Nuclear-Magnetic-Resonance Properties of the Staircase Kagome Antiferromagnet PbCu3TeO7 - 代佳 王朋帅 孙珊珊 庞斐 张金珊 董晓莉 乐艮 金魁 丛君状 孙阳 于伟强 (中国物理快报：英文版, 2015)
We report the first nuclear magnetic resonance （NMR） study on single crystals of staircase Kagome antiferromagnet PbCu3Te07 （TN1 -36K）. A Curie constant θ -140K is obtained by a Curie Weiss fit to the high- temperature Knight shift of 125 Te. The hyperfine coupling constant is estimated to be 125Ahf = -67 kOe/#B, and a strong interlayer coupling among staircase Kagome planes is suggested with such a large hyperfine coupling, according to the lattice structure. The 63,65Cu NMR spectra are found by the zero-field （ZF） NMR at T = 2 K, and the internal hyperfine fields are estimated to be 10.3 T and 9.6 T, for Cu（1） and Cu（2） sites, respectively, in the lattice. A second type of ZF NMFt signal with a large rf enhancement is also seen after field-cycling through a high magnetic field.